2018
DOI: 10.1177/0267658318770491
|View full text |Cite
|
Sign up to set email alerts
|

The role of native and non-native grammars in the comprehension of possessive pronouns

Abstract: Previous studies have shown that multilingual speakers are influenced by their native (L1) and non-native (L2) grammars when learning a new language. But, so far, these studies have mostly used untimed metalinguistic tasks. Here we examine whether multilinguals’ prior grammars also affect their sensitivity to morphosyntactic constraints during processing. We use speeded judgment and self-paced reading tasks to examine the comprehension of German possessive pronouns. To investigate whether native and non-native… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 78 publications
1
24
1
Order By: Relevance
“…By contrast, L2 influence only affected participants' judgment accuracy: L1 Spanish speakers of higher L2 English proficiency were more accurate detecting German possessor violations than less proficient speakers. Thus, L1 influence was seen Figure 2 An example of L1 and L2 influence in Ln morphosyntactic processing (Lago et al, 2019). L1 influence: compared to English natives, L1 Spanish speakers, whose native grammar lacks possessor gender agreement, showed smaller reading disruptions after infelicitous German possessives, consistent with inhibitory L1 influence.…”
Section: Bridging the Gapmentioning
confidence: 79%
See 1 more Smart Citation
“…By contrast, L2 influence only affected participants' judgment accuracy: L1 Spanish speakers of higher L2 English proficiency were more accurate detecting German possessor violations than less proficient speakers. Thus, L1 influence was seen Figure 2 An example of L1 and L2 influence in Ln morphosyntactic processing (Lago et al, 2019). L1 influence: compared to English natives, L1 Spanish speakers, whose native grammar lacks possessor gender agreement, showed smaller reading disruptions after infelicitous German possessives, consistent with inhibitory L1 influence.…”
Section: Bridging the Gapmentioning
confidence: 79%
“…Recently, we have started using processing methods to study Ln sentence comprehension (Lago, Garcia, & Felser, 2019). We examined the processing of German possessive pronouns like "ihren" in (3), which show a complex pattern of gender agreement: the stem of the pronoun (bolded) encodes possessor agreement, whereas the suffix (underlined) encodes possessee agreement (e.g., -en for a masculine possessee):…”
Section: Bridging the Gapmentioning
confidence: 99%
“…The CTR group completed the task remotely via a web link, and the bilinguals were tested in a quiet room, either in a lab or at their homes. It is true that the CTR group was not tested face-to-face (unlike the BIL group), but we note that web-based testing has been found to yield reliable results in many previous psycholinguistic studies (e.g., Enochson & Culbertson 2015;Gibson, Piantadosi & Fedorenko 2011;Dillon, Clifton & Frazier 2014;Wagers & Phillips 2014;Lago, Stutter Garcia & Felser 2019). Prior to the experiment, the BIL group filled in a demographic questionnaire including questions about their language history and use.…”
Section: Methodsmentioning
confidence: 99%
“…As for non-native comprehension of possessives, Lago et al (2018) investigated whether multilingual speakers with either L1-English/L2-Spanish or L1-Spanish/L2-English differ in their sensitivity to possessor agreement violations in German as an 'additional' non-native language ('La'), depending on whether possessor gender agreement is present in their L1 (English) or not (Spanish). Using context-free German sentences like (15a-d) in a speeded acceptability judgment and an implicit reading experiment, they found that (i) the L1-Spanish participants, as expected, showed less sensitivity than the L1-English group towards possessor-possessive mismatch as displayed in (15c-d); 12 (ii) high L2 proficiency may have helped L1-Spanish/L2-English in La-German but did not influence the performance of L1-English/L2-Spanish participants; (iii) contrary to their expectations, gender mismatch between possessive and possessee (Mutter 'mother'), as displayed in (15b,c) did not affect the L1-Spanish learners' performance in any significant way.…”
Section: Osla Volume 12(2) 2021mentioning
confidence: 99%
“…French but with English as a prominent exception, adnominal possessives exhibit feature (number, gender, case, …) agreement with the head noun of their host DP (the possessee), in addition to being specified for antecedent features. Beside searching for an antecedent (the possessor), then, comprehenders must 'keep an eye' on the possessee noun (phrase) too, checking for the relevant features; as pointed out by Lago et al (2018), however, possessee agreement is probably a bigger problem in production than in comprehension. 10 As far as challenges to L2 acquisition are concerned, then, the grammar of adnominal possessives opens up for more variation across L1/L2 pairs than ordinary pronouns -including the relative order of possessive and possessee (cf.…”
mentioning
confidence: 99%